2015
DOI: 10.1261/rna.052340.115
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the core mitochondrial RNA-binding complex 1 is vital for trypanosome RNA editing

Abstract: Trypanosoma brucei is the causative agent of the human and veterinarian diseases African sleeping sickness and nagana. A majority of its mitochondrial-encoded transcripts undergo RNA editing, an essential process of post-transcriptional uridine insertion and deletion to produce translatable mRNA. Besides the well-characterized RNA editing core complex, the mitochondrial RNA-binding 1 (MRB1) complex is one of the key players. It comprises a core complex of about six proteins, guide RNA-associated proteins (GAPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 51 publications
2
32
1
Order By: Relevance
“…Mass spectrometry studies by these authors indicate that MRB8620 maintains numerous contacts with the large ribosomal subunit; thus, it may play a more substantial role in post‐editing events than other MRB1 core components. However, a more recent study has shown that RNAi‐mediated repression of MRB8620 indeed results in an inhibition of editing due to the comprised integrity of the MRB1 core, albeit to a lesser degree than when the other studied core MRB1 subunits are downregulated . In this background, transcripts requiring RNA editing accumulated on the GAP1/2 heterotetramer, indicating a disruption of RNA trafficking during the RNA editing process when the MRB1 core is disrupted.…”
Section: Mrb1 Complex Functionmentioning
confidence: 95%
See 3 more Smart Citations
“…Mass spectrometry studies by these authors indicate that MRB8620 maintains numerous contacts with the large ribosomal subunit; thus, it may play a more substantial role in post‐editing events than other MRB1 core components. However, a more recent study has shown that RNAi‐mediated repression of MRB8620 indeed results in an inhibition of editing due to the comprised integrity of the MRB1 core, albeit to a lesser degree than when the other studied core MRB1 subunits are downregulated . In this background, transcripts requiring RNA editing accumulated on the GAP1/2 heterotetramer, indicating a disruption of RNA trafficking during the RNA editing process when the MRB1 core is disrupted.…”
Section: Mrb1 Complex Functionmentioning
confidence: 95%
“…Indeed, in addition to their roles as integral MRB1 core components, GAP1/2 are present in association with the REH2 RNA helicase and, separately, the TbRGG3 RNA binding protein in the absence of some MRB1 core components, suggesting additional roles for GAP1/2 in mt RNA metabolism in addition to their functions in the MRB1 core. Furthermore, GAP1/2 downregulation does not appear to affect the interaction of the other MRB1 core subunits with each other . The incorporation of GAP1/2 into higher molecular weight complexes, like other MRB1 components, requires mt RNA …”
Section: Architecture Of the Mrb1 Complexmentioning
confidence: 95%
See 2 more Smart Citations
“…Though RECC is necessary for the editing process, it is not sufficient. Numerous recent studies have demonstrated that a large, possibly dynamic and heterogeneous complex termed MRB1 (mitochondrial RNA binding complex 1) or RESC (RNA editing substrate binding complex) is also essential for RNA editing in kinetoplastids (Fisk et al 2008;Hashimi et al 2008Hashimi et al , 2009Hashimi et al , 2013Weng et al 2008;Acestor et al 2009;Ammerman et al 2011Ammerman et al , 2012Ammerman et al , 2013Kafkova et al 2012;Aphasizheva et al 2014;Huang et al 2015;Madina et al 2015;Read et al 2016). Indeed, the MRB1 complex likely acts as the platform for RNA editing, since it contains readily detectable mRNA and gRNA, while purified RECC lacks associated RNA (Weng et al 2008;Aphasizheva et al 2014;Madina et al 2014Madina et al , 2015.…”
Section: Introductionmentioning
confidence: 99%